P560 Multi-centric randomised study comparing interventional vs. non-interventional treatment for anal fistulas in patient with Crohn's disease and adalimumab treatment. (25th January 2019) - Abramowitz, L; Bouchard, D; Siproudhis, L; Pigot, F; Roumeguere-Blond, P; Pillant, H; Vinson-Bonnet, B; Faucheron, J-L; Senejoux, A; Bonnaud, G; Meurette, G; Train, C; et al.
Abstract: Background: Anal fistulas negatively impact prognostic in patients with Crohn's disease. Recommended initial treatment associates surgical drainage with seton insertion, and biotherapy to control luminal and anal disease activity. After this preliminary treatment, options concerning fistula tract treatment are still debated. Especially surgical tract closure efficacy has been rarely evaluated, and not always in patients under biotherapy. Methods: In this prospective, multi-centric study, all patients with an anal fistula having responded to an initial treatment by drainage and seton insertion, plus adalimumab injections (ADA) were randomised between sole seton ablation or surgical closure of the tract by any technique (glue, flap, LIFT, etc.). Patients were included when local conditions indicated inflammatory remission (no abscess, minimal drainage) after at least a 3 month treatment with ADA, without active luminal disease. Main end-point was fistula closure at 12 months (Present criteria). Secondary end-points were ano-perineal symptoms PDAI score, quality of life IBDQ score, continence Wexner score, and perineal RMN evaluation at 6 and 12 months. Results: Sixty-four patients (24M, 40F), mean age 36 years (19–63) have been randomised (31 sole seton ablation vs. 33 seton ablation plus surgical fistula tract closure). Fistulas were classified as simple and complex in respectively 16 (25%), and 48 patients (75%) (including 8 ano-vaginal). At 3, 6, and 12 months, fistula healing was obtained in, respectively 56%, 59%, and 59% of the patients, without any significant difference between sole seton ablation or fistula closure. In patients with simple and complex fistulas rates were respectively. 69%, 80%, and 80%, and 51%, 52%, and 52% ( p = 0.035 at 12 months between simple and complex fistulas), with no difference between the two arms in any category of fistulas. Initial and 12 month mean PDAI score were 11 [9–20] and 6 [8–18] ( p < 0.0001) after seton ablation, and 12 [7–21] and 8 [5–16] ( p < 0.0001) after fistula closure, without any difference between the two arms. At 12 months RMN demonstrated no hyperfixation after gadolinium injection in 82% of the patients with a closed fistula, without any difference between the two arms. At 12 months Van Assche and Wexner scores were not different between the two arms. IBDQ did not change during follow-up and was not different between the two arms. Conclusions: In patients with Crohn's disease and an anal fistula, having responded to initial treatment with surgical drainage and ADA injections, healing rates at 12 months were not different after closure of the fistula tract or simple seton ablation. Globally at 1 year under ADA treatment, healing rates for simple and complex anal fistulas were, respectively, 80% and 50%.